Polymorphism at the nestling stage and host‐specific mimicry in an Australasian cuckoo‐host arms race. Issue 1 (11th December 2022) - Attisano, Alfredo; Gill, Brian J.; Anderson, Michael G.; Gula, Roman; Langmore, Naomi E.; Okahisa, Yuji; Sato, Nozomu J.; Tanaka, Keita D.; Thorogood, Rose; Ueda, Keisuke; Theuerkauf, Jörn
Abstract: Decades of research have shown that the coevolutionary arms race between avian brood parasites and their hosts can promote phenotypic diversification in hosts and brood parasites. However, relatively little is known about the role of brood parasitism in promoting phenotypic diversification of nestlings. We review field data collected over four decades in Australia, New Caledonia and New Zealand to assess potential for coevolutionary interactions between the shining bronze‐cuckoo ( Chalcites lucidus ) and its hosts, and how diversification at the nestling stage may be generating different subspecies. The shining bronze‐cuckoo is a specialist parasite of a few hosts in the family Acanthizidae. It has diversified into subspecies, of which the nestlings closely mimic the respective host nestlings in each region. Additionally, some cuckoo subspecies have polymorphic nestlings. The Acanthizidae hosts have similar breeding and nesting habits and only moderately effective frontline defences against parasitism at cuckoo egg laying or at the egg stages. However, some hosts have developed highly effective defences at the nestling stage by recognising and ejecting cuckoo nestlings from the nest. As with the cuckoo nestlings, some hosts have polymorphic nestlings. The coevolutionary interactions in each region suggest different evolutionary stages of the arms race in which either the parasite or the host is currently in the lead. The presence of moderately effective defences at the egg laying and egg stages might explain why some hosts do not have defences at the nestling stage. The south‐Pacific cuckoo – host systems are excellent models to explore the evolutionary mechanisms driving the diversification at the nestling stage in the coevolutionary arms race between avian brood parasites and their hosts. Abstract : Brood parasitism promotes diversification in brood parasites and hosts. The authors show nestling phenotypic diversification in the shining cuckoo and its hosts from the South‐Pacific, and how this might generate different subspecies.